2018
DOI: 10.1287/mnsc.2017.2783
|View full text |Cite
|
Sign up to set email alerts
|

Pricing of Conditional Upgrades in the Presence of Strategic Consumers

Abstract: In this paper, we study a conditional upgrade strategy that has recently become very common in the travel industry. After a consumer makes a reservation for a product (e.g., a hotel room), she is asked whether she would like to upgrade her product to a higher-quality (more expensive) one at a discounted price. The upgrade, however, is not fulfilled immediately. The firm fulfills upgrades at check-in if higher-quality products are still available, and the upgrade fee is only charged to the consumer if she gets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Extant research on upselling has mainly focused on the offline setting, offering limited insights into online upselling (Denizci Guillet, 2020). Prior research on online upselling has investigated optimal pricing strategies in the presence of different consumer types (Cui et al , 2017), the effect of consumer types and market size of premium rooms on boosting revenue (Yilmaz et al , 2017) and the comparison of online and offline upselling on generating additional hotel revenue (Denizci Guillet, 2020). While these studies showcase the importance of online upselling, little is known about when and how to make online upselling successful from the consumer’s perspective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research on upselling has mainly focused on the offline setting, offering limited insights into online upselling (Denizci Guillet, 2020). Prior research on online upselling has investigated optimal pricing strategies in the presence of different consumer types (Cui et al , 2017), the effect of consumer types and market size of premium rooms on boosting revenue (Yilmaz et al , 2017) and the comparison of online and offline upselling on generating additional hotel revenue (Denizci Guillet, 2020). While these studies showcase the importance of online upselling, little is known about when and how to make online upselling successful from the consumer’s perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Further, while a preliminary study on upselling has revealed the different upselling effectiveness between the time immediately after the booking and the time at check-in, the underlying reasons remained unknown (Cui et al , 2017). This research reveals the underlying mechanism that explains why consumers respond differently to upselling promotions offered at different points in time.…”
Section: Discussionmentioning
confidence: 99%
“…Cachon and Swinney [16] have studied purchasing, pricing, and quick response in relation to strategic consumers. Cui et al [17] have considered the pricing of conditional upgrades in relation to strategic consumers. Numerous studies have also examined strategic (forward-looking) and non-strategic (myopic) customers [12], [14], [18]- [23].…”
Section: B the Different Types Of Consumersmentioning
confidence: 99%
“…There is also a related stream of work on pricing and upselling, in which a customer is required to make a side payment to receive a higher value product. For examples of recent work on upselling, we refer the reader to Aydin and Ziya (2008), Gallego and Stefanescu (2009), and Cui et al (2017).…”
Section: Related Literaturementioning
confidence: 99%